Using Persuasive Words in Influencer Tasya Farasya's Instagram Content to Attract Consumer Interest in Skincare Cosmetic Products - Fitriyah Qolbi, Mauritsa; Iklimah, Nadiyah; Cahyani , Cucu Gina; Hindun, Hindun (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe and find out persuasive sentences contained in content on Instagram social media. This research was conducted using qualitative descriptive methods. The data used in this study are all aspects related to persuasive sentences in the video endorse of Tasya Farasya's Instagram account. The source of this research data is sentences on Tasya Farasya's Instagram account in the form of primary data from books and journal articles, while secondary data from Tasya Farasya's Instagram content collected by listening to record techniques. The results showed that there were 63 persuasive sentences and researchers classified the persuasive sentences obtained into 4 categories.